Applied Biotechnology: Isolation and Detection of an Efficient Biosurfactant from Pseudomonas sp. Comparative Studies against Chemical Surfactants - Mainez, María Esperanza (2017)
The use of biosurfactants became essential because of its multiple properties and applications. The high toxicity to the environment led to search for new alternatives such as the reduction or replacement by biological surfactants. Because of this, it is in our interest to produce biosurfactants from a non-pathogenic Pseudomonas. We obtained lower values of critical micelle concentration (CMC) from the culture broth than obtained from dodecyl sulfate sodium (SDS) and Pluronic F-68, used as pure surfactans. We found values of critical micellar concentration close to 0.15 mg/L in the purified fraction by adsorption chromatography. We determine by mass spectrometry this strain possibly produces two families of biosurfactants. Majority fraction might be formed by cyclic lipopeptides whose molecular weights could be located in the range of 1100-1200 Da. However, it is necessary perform confirmatory structural studies and to determine the specific structure of these analytes.